ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI PERBANDINGAN PADA KELAS V SDN 106815 MARINDAL - Listri Amelia; Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the level of students difficulty in solving story problems oncomparative material in grade V of SDN 106815 Marindal. The method used is descriptivequalitative research, with participants consisting of 28 grade V students. The instrumentsused include story problem tests, interviews, and observations. The results showed that15 out of 28 students were identified as having difficulties in five categories based onNewmans theory. The type of difficulty in reading questions was 4.6% (low category),while errors in understanding questions reached 84.6%, transformation errors 76%,calculation errors 82.6%, and errors in writing conclusions 90% (all included in the highcategory). In addition, 53.3% of students showed low motivation, 33.3% experiencedcarelessness, and 66.6% considered story problems more difficult than number problems.Factors causing difficulties include internal factors such as intelligence and mastery ofconcepts, as well as external factors such as learning methods, learning media, andparental attention. Efforts that can be made by teachers to overcome these difficultiesinclude improving conceptual understanding through interactive learning methods,increasing story problem exercises, and providing more motivation and support tostudents. This study is expected to provide insight for teachers in designing more effectivelearning strategies to help students overcome difficulties in story problems on comparativematerial.